Effects of Sub-Lethal Concentrations of Oxytetracycline and Erythromycin on Antioxidant Enzymes in Cyprinus Carpio - Rehman, Rimsha; Qayyum, Nayab; Waqar, Muhammad; Khatoon, Javaria; Bhatti, Rafia Munir; Ambreen, Shawana; Bakhtawar, Pakeeza; Ahmad, Rizwan; Khan, Saleena; Sultan, Mohsin; Shahzadi, Irum; Hassan, Rana Qadir Ul (Biological and Clinical Sciences Research Journal, 2025)
Accumulation of antibiotics in freshwater bodies poses a major ecological threat, as excessive antimicrobial residues induce oxidative stress in aquatic organisms, particularly fish. The antioxidant defence system plays a crucial role in mitigating such stress responses. Objective: To evaluate the effects of oxytetracycline and erythromycin on the activity of antioxidant enzymes in common carp (Cyprinus carpio).Methods: A laboratory-based experiment was conducted using common carp collected from a local fish pond and acclimatized for 10 days under controlled conditions. Fish were exposed for 96 hours to sub-lethal concentrations of oxytetracycline and erythromycin in separate treatment groups, along with a control group. Each group consisted of three replications maintained under identical physicochemical conditions. Antioxidant enzyme activities of superoxide dismutase and peroxidase were quantified in selected organs using a visible spectrophotometer at 560 nm and 470 nm, respectively. Data were analyzed using a two-way ANOVA, followed by Tukey's HSD for mean comparisons. Correlation analysis was performed to determine associations among study variables. Results: A significant reduction in superoxide dismutase and peroxidase activity was observed at 72 and 96 hours of exposure in both antibiotic-treated groups compared with controls (p<0.05). Oxytetracycline exhibited a stronger inhibitory effect on antioxidant responses, consistent with enhanced reactive oxygen species generation. Increasing antibiotic concentration led to a marked decline in enzyme activity across both treatment groups. Conclusion: Acute exposure to oxytetracycline and erythromycin leads to oxidative stress in common carp by suppressing key antioxidant enzymes, indicating that antibiotic pollution in aquatic environments may compromise fish health and physiological homeostasis.